Spinal Dural Arteriovenous Fistula in a Pediatric Patient with History of Endovascular Therapy Failure: A Case Report - Primadenny Ariesa Airlangga, M.D, M.Sc; Rizal Alexander Lisan; Aries Rakhmat Hidayat (Faculty of Medicine, Universitas Airlangga, 2023)
Spinal Dural Arteriovenous Fistula (SDAVF) cases in children are extremely rare and pose a high risk for intraoperative hemorrhage. The clinical manifestation and imaging results may be vague and deceptive, frequently mistaken for other conditions such as demyelinating or spinal degenerative illnesses. SDAVF's cause is not well understood. Here, we present the case of a 10-year-old male patient with SDAVF who did not improve after endovascular therapy. The patient complained of weakness in the lower extremities, skin thickness, tingling sensations, and painful bowel movements and urination. The patient underwent endovascular embolization due to spinal AVF from the 9th thoracic vertebrae until the sacral vertebrae one month earlier. But no significant clinical improvement was found. The vital signs of the patient were within normal limits. An MRI showed a flow-void lesion with tortuosity in the dorsal spinal area at the 9th and 10th thoracic vertebrae. Because an embolization procedure was performed on the patient, which resulted in no significant improvement, it was planned for the patient to undergo an MRI and MRA evaluation. An MRI and MRA later showed the formation of an extramedullary intradural cyst at levels T9 to T10 of the thoracic vertebrae. Decompression surgery (left hemilaminectomy) and tumor extirpation were thereafter carried out on the patient after the routine laboratory test was performed. After the procedure, the patient showed improvement and could carry out everyday activities independently at 10 months post-operatively. The failure of endovascular therapy can be attributed to several factors, such as the surgeon's experience, tools, and embolization technique, and follow-up treatment by surgery.